Inverse wavefield transform of vertical magnetic component of loop-source TEM data over coalfield strata: a case study in Inner Mongolia, China - Guo, Jianlei; Fan, Kerui; Li, Wenhan; Xue, Junjie; Lu, Kailiang; Qi, Zhipeng; Li, Xiu (Journal of geophysics and engineering, 2025)
The transient electromagnetic method (TEM) is an effective and efficient tool that can be used to map the subsurface distribution of electric conductivity. To highlight the subsurface conductivity contrasts, inverse wavefield transform has been proposed and applied to provide reflection events from geo-electric interfaces similar to those in the wavefield reflection methods. In this paper we present a case study of inverse wavefield transform for loop-source TEM data. The TEM survey site is located in a coal field in Inner Mongolia, China. Previous geological surveys and TEM data inversion had already confirmed that, within the depth of 800 m, the subsurface structure of conductivity is layered and smooth. The numerical and field data were transformed by a self-adapted algorithm of inverse wavefield transform. The reflection events were observed as expected in the pseudo-wavefield wavefield traces transformed from the numerical and field data. The data misfit between the fitted data (recovered from the transformed pseudo-wavefield) and the field (or numerical) data was smaller than 15% for the 720 × 720 m loop used in our case. Finally, numerical and field cases with detailed discussion are presented to illustrate that the algorithm and results of our inverse wavefield transform are physically rational and numerically accurate.